Himpunan hadith akhir zaman yang Pertama: Nu`Aym bin Hammād Al-Marwazī (m. 228h) dan kitab Al-Fitan Wa Al-Malāḥim - Ali Abdul Jalil; Umar Muhammad Noor (Universiti Sains Islam Malaysia, 2024)
Nu`aym bin Ḥammād is one of the famous scholars who made important contributions in hadith and Islamic belief. His book al-Fitan wa al-Malāḥim is considered the earliest work on great calamities before the end times. However, Nu`aym and his book have been criticized by previous and current hadith scholars. This study was conducted with the aim of studying Nu`aym's character and the position of his book al-Fitan. In order to achieve this goal, a qualitative method is used by analyzing the content that were found in scholarly writings about Nu`aym and the position of his book al-Fitan. This study shows that Nu`aym is a ṣadūq hadith narrator but makes many mistakes. His firmness in opposing the Jahmiyyah group caused him to die in government custody. As for his book, there are several political slanders and natural phenomena that prompted him to write this book alFitan. However, hadith scholars stated that this book contains many hadiths that are not reliable, and people must be careful when referring to them.